Asuhan Kebidanan Komprehensif pada Ny. I Umur 33 Tahun dengan Riwayat Sectio Caesarea di Puskesmas Sirampog Kabupaten Brebes Tahun 2024 - Melisa Melisa; Endang Susilowati; Nurhidayah Nurhidayah (Lembaga Pengembangan Kinerja Dosen, 2025)
(MMR) refers to the number of deaths of women that occur during the pregnancy period or within 42 days after delivery. According to WHO in (2022) MMR is an indicator that states the number of maternal deaths for 303,000 per 100.000 live births, According to the Brebes health office (2022) MMR 177.94/ 100.000 live birth, IMR 197 cases. According to data obtained from the Sirampog Health Center daring 2022, the maternal mortality rate was recorded at one case, and eleven infant dealths. The study aims to provide comprehensive midwifery care to patients with a history of cesarean section, using a qualitative descriptive case study approach. Based on integrate midwifery care carried out on patients who had a history of cesarean section, the results were obtained, namely Mrs. Saya’s pregnancy with an indication of CPD as well as high blood pressure and ureine protein approaching positive one. Delivery was carried out by secarean section as an effort to prevent complications in the mother anda baby. During the neonatal care period up to 28 days of age, no abdormalities or problems were found. During the postpartum period up to 42 days, on problem or complications were found. Mrs. I chose to use an IUD as a contraceptive.